Taking Action on Screen Time: Phone-Free Classrooms and Other Steps to Improve Youth Mental Health, Attention, and Academics - Rybakova, Katie (Maine Policy Review, 2025)
Youth spend an inordinate amount of time on phones and other screen-based devices; yet research shows myriad negative effects of this behavior on education and general health of young people. This commentary highlights the evidence on how excess screen time affects youth from birth to late teens and provide suggestions for actionable change, including the possible merit of school phone bans, community digital detox spaces, scrutiny of adult screen time habits as models for youth, and green time (time spent outdoors) to counteract negative impacts of increased screen time.
Keywords: screen time; phone-free schools; digital detox